Bacillus subtilis ameliorates Escherichia coli-induced endometritis in mice via maintaining endometrial barrier and inhibiting inflammatory response. (May 2022) - Li, Shuang; Wang, Yiqi; Feng, Lianjun; Yu, Zhongxian; Qiu, Min; Wang, Ying; Zhang, Naisheng; Hu, Xiaoyu; Fu, Yunhe
Abstract: Endometritis is a common obstetric disease that occurs most frequently after parturition in a variety of animals. Animal infertility due to endometritis severely hinders animal husbandry and often causes serious economic losses to the dairy farming industry. According to reports, Bacillus subtilis ( B. subtilis ) can prevent pathogenic colonization of epithelial cells and exert immunostimulatory effects. The present study aimed to reveal the protective effect of B. subtilis on endometritis induced by Escherichia coli ( E. coli ) in mice. The experimental model required in this experiment was established by injecting E. coli intrauterinely, and different concentrations of B. subtilis H28 were administered 10 days before E. coli injection. The pathological changes in the uterine tissue of mice were assessed by haematoxylin-eosin (H&E) staining. Myeloperoxidase (MPO) activity measurements and enzyme-linked immunosorbent assay (ELISA) based measurement of pro-inflammatory cytokines levels were performed. Activation of NF-κB signaling pathway were detected by Western blot, and the changes in the levels of tight junction proteins (TJPs) was analyzed using Western blot detection and quantitative real-time polymerase chain reaction (qRT–PCR). As seen from the results, B. subtilis H28 pretreatment decreased uterine neutrophil infiltration, IL-1β and TNF-α production, and the NF-κB activation during endometritis induced by E. coli . In addition, B. subtilis H28 significantly increased the expression of the tight junction proteins ZO-1, claudin-3 and occludin in uterine infected with E. coli . In conclusion, in the present study, we found that B. subtilis H28 ameliorated E. coli -induced endometritis by maintaining the endometrial barrier and inhibiting the inflammatory response. Highlights: Bacillus subtilis H28 reduced the uterus pathological injury and proinflammation cytokine production during endometritis induced by E. coli . Bacillus subtilis H28 reduced the uterus barrier permeability by increased the expression of claudin-3, occludin, and ZO-1. Bacillus subtilis H28 inhibited the activation of the NF-κB signalling pathway, and ultimately reducing inflammation in uterus induced by E. coli .